Robotic assembly of modular concrete shells using falsework - Egor Ivaniuk; Dmytro Pukhkaiev; Mathias Reichle; Wanqi Zhao; Johannes Mey; Manuel Krombholz; Zlata Tošić; Uwe Aßmann; Sven Klinkel; Viktor Mechtcherine (Developments in the Built Environment)
The rapid development of robotics has the potential to transform the construction industry of the future. One possible application of robots is the assembly of modular concrete shells. This type of structure saves materials, while the modular approach makes them more cost-effective by eliminating the need for formwork. So far, however, robots have struggled to accurately position modules when assembling large modular shells on the construction site. The authors propose an alternative approach to the robotic assembly of modular shells based on the use of modular falsework. The presence of a falsework enables the creation of large-scale shells of complex shapes out of an unlimited number of modules while ensuring the accuracy of their positioning. This paper describes a possible methodology for implementing this approach and validates it by assembling a demonstrator, as well as presents the results of static and dynamic analysis of the modules moved by the robot.